Materials on the fauna of the terrestrial invertebrates of the technogenical landscapes of Northern Balkhash - Абукенова, В.С.; Реверт, И.В. (Fundamental and Experimental Biology, 2015)
Invertebrate animals are the important and poorly studied component of the semi-desert ecosystems of Kazakhstan. Entomofauna and the other groups are traditionally used for bioindication of anthropogenic and man-caused pollution. The fauna of invertebrates of Northern Balkhash has been studied in connection with the use of land for the recovery of activity-industrial complex. The buffer zone has been allocated as the unmodified natural landscape. Our study of the fauna at the level of large taxa showed the dependence of the distribution of invertebrates from the ecological status of biocenoses. The article presents the results of determination of the dynamic density and trophic structure of invertebrates.